The role of relationship marketing and brand love among banking consumers in an emerging market context - Panduro-Ramirez, Jose Alberto (2024)
Relationship marketing is a concept that focuses not only on increasing the volume of relationship transactions, but also on improving consumer perception. Therefore, this research aimed to evaluate the influence of relationship marketing dimensions on brand love. An explanatory study was conducted considering 417 participants who confirmed their affiliation with a bank. Adults aged between 18 and 52 years participated in the study. Data were collected using a selfadministered relationship marketing and brand love form, obtaining an adequate measurement model (α = between 0.842 and 0.908; CR = between 0.905 and 0.942; AVE = 0.679 and 0.845; VIFs = between 1.638 and 2.802). The theoretical model was evaluated using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. According to the results, the hypotheses were confirmed, demonstrating the positive influence of trust (β = 0.40), commitment (β = 0.08), communication (β = 0.12), and conflict management (β = 0.08) on brand love. These results demonstrated that trust, as a dimension of relationship marketing, guarantees a greater contribution to the structural model. The implementation of relationship marketing practices and strategies that emphasize trust by banks can strengthen brand love and foster developing markets in an emerging economy. Although previous studies have analyzed some factors that influence brand love, the topic has not been examined from a relationship marketing perspective, which provides valuable insights for the banking industry, stakeholders, academy, and leaders in business administration.